Integration of Digital Health, Telemedicine, and Healthcare Service Management: Implications for Quality of Care and Health System Sustainability – A Scoping Review - Jeki Purnomo; Nurfalia Harfah; Irfan Kurniawan (Hayyan Journal, 2026)
Background: Digital health and telemedicine have evolved into structural components of modern healthcare systems, fundamentally transforming how access, service delivery, and care coordination are organized. While their adoption accelerated during the COVID-19 pandemic, their broader implications for healthcare service management, quality of care, and system sustainability remain variably understood. Aim: This scoping review aims to synthesize current evidence on the integration of digital health, telemedicine, and healthcare service management, with a focus on their impact on quality of care and health system sustainability. Methods: A scoping review design was applied following PRISMA-oriented principles. Literature published between 2020 and 2026 was identified from major scientific databases, including PubMed, Scopus, and ScienceDirect. Studies were included if they examined digital health or telemedicine interventions and reported outcomes related to healthcare access, service quality, patient experience, efficiency, or sustainability. Evidence was synthesized across four domains: digital health ecosystem, access to care, service quality, and efficiency–sustainability. Results: The findings indicate that digital health and telemedicine expand healthcare access by reducing geographical and temporal barriers, improve service quality through enhanced coordination and communication, and increase operational efficiency by optimizing resource utilization and reducing unnecessary hospital visits. In addition, digital health contributes to system sustainability by enabling flexible, adaptive service delivery models and improving system resilience. However, these benefits are conditional on factors such as infrastructure readiness, interoperability, governance frameworks, and digital equity. Conclusion: Digital health and telemedicine should be conceptualized as healthcare service-management infrastructure rather than standalone technologies. Their impact on quality and sustainability depends on effective integration with clinical workflows, organizational processes, and policy frameworks. Future health systems must focus on governance, equity, and continuous performance evaluation to realize the full potential of digital transformation.